Avoiding information about one's romantic partner. (February 2021) - Hussain, Maryam; Price, Devon M.; Gesselman, Amanda N.; Shepperd, James A.; Howell, Jennifer L.
Research links open communication and self-disclosure to a host of beneficial outcomes in romantic relationships, including better relationship quality, relationship satisfaction, feelings of closeness and commitment, and relationship longevity. However, learning some information about a partner may evoke negative consequences. In two studies, we examined the types of information people may wish to avoid learning about their past or current romantic partners (Study 1), and individual differences in avoidance of information about a current romantic partner (Study 2). Content-coding of data from Study 1 revealed that a majority (51%) of respondents wished to avoid information related to their partner's history of sexual behavior and/or infidelity. In Study 2, participants who were older and who scored higher on measures of anxious and avoidant attachment were more likely to want to avoid information about their partner. Furthermore, replicating and extending Study 1, participants most wished to avoid information about their partners' prior sexual behavior and/or infidelity, as well as their partners' prejudices. We interpret our findings in terms of a threat-management framework for information avoidance, suggesting that threats to the self and relationship may influence the decision to avoid information about a romantic partner.